Humanity : a moral history of the twentieth century - Glover, Jonathan (Yale University Press, 2000)
The twentieth century was the most brutal in human history, featuring a litany of shameful events that includes the Holocaust, Hiroshima, the Stalinist era, Cambodia, Yugoslavia, and Rwanda. This important book looks at the politics of our times and the roots of human nature to discover why so many atrocities were perpetuated and how we can create a social environment to prevent their recurrence. Jonathan Glover finds similarities in the psychology of those who perpetuate, collaborate in, and are complicit with atrocities, uncovering some disturbing common elements--tribal hatred, blind adherence to ideology, diminished personal responsibility--as well as characteristics unique to each situation. Acknowledging that human nature has a dark and destructive side, he proposes that we encourage the development of a political and personal moral imagination that will compel us to refrain from and protest all acts of cruelty.